ANALISIS FILOGENETIK KERBAU LOKAL LOMBOK TENGAH (Bubalus bubalis) BERDASARKAN PENANDA DNA MIKROSATELIT - Sukri, Akhmad (Jurnal Florea, 2014)
This study examines the phylogenetic relationships of two populations of Central Lombok local buffalo (Bubalus bubalis) through microsatellite DNA markers based on three random primers, namely HEL09, INRA 023 and INRA 032. Grouping several individual buffalo from the two populations into one cluster showed genetic mixing. The existence of genetic mixing allegedly because the buffalo population is spread open local population. Many buffalo imported from other populations in Central Lombok district or from other areas by farmers to be maintained along with buffalos that already exist, resulting in mixing or close relatives outside marriage among individual local buffalo of Central Lombok. Keywords : phylogenetic analysis, Bubalus bubalis, microsatellite